BS EN 2882. Aerospace series. Nuts, hexagonal, self-locking, with counterbore and captive washer, in steel, cadmium plated, MoS2 lubricated. Classification: 1 100 MPa (at ambient temperature) / 235 °C. (28th October 2021) - British Standards Institution,
No abstract available